Evaluating Cognitive Absorption, Technology Acceptance, and Online Educational Software Usability of Students in Online Programming Courses - Toraman, Di̇lber Cansu (ProQuest Dissertations & Theses, 2023)
This thesis examines the online self-learning, cognitive absorption, and technology acceptance models of students in online programming courses. This thesis discussed the role and impact of various factors on the learning of programming students. Besides investigating the effect of the educational learning-based online course content of Comp109 Introduction to Programming (Java), Comp110 Object Oriented Programming ve Comp210 Data Structures and Algorithms courses on student success, the effects of students' cognitive absorption, the acceptance, and usability of educational online learning environments were discussed. The subjects of the research are a total of 181 online students in the student group. The researcher carried out the application of the questionnaire tools to the students in the programming courses. Based on the questionnaires, this research aims to examine the effect of students' cognitive absorption, technology acceptance, and online educational software usability on student success in programming courses. In this study, the following scales were applied in the survey measurements, respectively: Cognitive absorption scale (13 items), technology acceptance model (14 items), online educational software usability (39 items). The preparation, ethical approval and implementation of the relevant survey and data analysis research took three months. This study evaluates students' cognitive assimilation, technology acceptance, and e-education software usability scale and suitability for online education in online programming courses. Each of these three scales was examined from seven different perspectives: Gender, Course Code, Department, Age, Expertise, Frequency of Internet use, and Interest in technology. Normality test, ANOVA, Mann-Whitney U Test and Kruskal Wallis Test were used to compare and evaluate these measurements. In addition to these test measurements, the MANOVA test was also applied for multivariate analysis. MANOVA test was carried out in detail from 4 different perspectives. The results of each of these scales were investigated from seven different perspectives and compared with related studies, and suggestions were presented based on the obtained results. In line with my findings, the positive effect of online programming courses on cognitive absorption has been demonstrated. However, it was also shown that there was no significant difference between demographic variables. In addition to these, a literature search was made for all three scales for discussion and a discussion was written. Results are written according to the discussion and analysis.